Universal history in fourteenth-century Iceland: studies in AM 764 4to. - Oskarsdottir, S (University of London, 2000)
The thesis is a philological examination of the first part of the manuscript AM 764 4to, written in Northern Iceland in the latter half of the fourteenth-century. The first part of the dissertation deals with paleographical and orthographical features of the codex which reveal that the book was in all likelihood produced in a scriptorium in Skagafjorior c. 1376-1386. An overview is given of previous scholarship concerning the manuscript and its content. The main section is devoted to discussion of the content of folios 1-23o f the codex. It is argued that instead of being a haphazard collection of unrelated texts, the first half of the book was conceived as a whole, and that the aim of the scribes was to produce a survey of the history of the world organised into aetates mundi. The sources for the different passages in this history are clarified and the scribes' treatment of these sources is viewed against parallel Old Norse works. Special attention is devoted to Bible translations. The third section begins with an overview of the development of universal history in the Middle Ages which subsequently serves as a basis for discussion of the place AM 764 4to has within this tradition, with regard to Latin works as well as vernacular ones. It is argued that the book was written for the nunnery at Reynistaour in Skagafjoror and may have served as a schoolbook. The last part of the thesis contains a diplomatic transcription of the text of folios 1-23v4.